ANALISIS HUBUNGAN ANTARA MOTIVASI BELAJAR DENGAN HASIL BELAJAR SISWA PADA SEKOLAH DASAR NEGERI 3 ALLAKUANG KECAMATAN MARITENGNGAE KABUPATEN SIDENRENG RAPPANG - Damis, Damis; Muhajis, Muhajis (Idaarah: Jurnal Manajemen Pendidikan, 2019)
Abstract: This study aims to find out and analyze the relationship between learning motivation and student learning outcomes at State Elementary School 3 Allakuang, Maritengngae District, Sidenreng Rappang Regency. This research is quantitative research by distributing questionnaires to 44 students. This study used a simple linear regression analysis method to determine the effect of learning motivation on student learning achievement, and correlation coefficient to measure the relationship between one variable and another variable. The results showed that motivation had a significant influence on student learning achievement and there was a positive relationship between learning motivation towards student learning outcomes, but the relationship was weak because the results of the discussion showed a relationship between learning motivation and student learning outcomes of 0.10 or 10%.